2019
DOI: 10.1080/21691401.2018.1553885
|View full text |Cite
|
Sign up to set email alerts
|

Pain management using nanotechnology approaches

Abstract: The proper treatment of pain is yet a major medical challenge. To obtain a long-term analgesia action, opioid therapy is the gold standard therapy for overcoming a chronic pain. Nanotechnology focus on formulating therapeutic agents encapsulated in a biocompatible nanocarriers (10-200 nanometer), these include but not limited to nanoparticles, liposomes and nanocapsules, micelles, dendrimers and nanotubes. This review gives an overview of current strategies of pain treatment with the help of the knowledge of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…The specificity of antidepressants can be amended by conjugating a ligand covalently to the polymeric nanoparticles [ 23 ]. As a drug carrier, it displays sustained drug release, biodegradability, prolonged duration, ability to deliver peptides, proteins, and genes through the oral route of administration, and high stability during storage [ 23 , 73 ]. Moreover, polymeric nanoparticles can cross the BBB via receptor-mediated endocytosis [ 74 ].…”
Section: Nanocarriers Employed As Therapeutic Delivery Platforms Of Antidepressantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The specificity of antidepressants can be amended by conjugating a ligand covalently to the polymeric nanoparticles [ 23 ]. As a drug carrier, it displays sustained drug release, biodegradability, prolonged duration, ability to deliver peptides, proteins, and genes through the oral route of administration, and high stability during storage [ 23 , 73 ]. Moreover, polymeric nanoparticles can cross the BBB via receptor-mediated endocytosis [ 74 ].…”
Section: Nanocarriers Employed As Therapeutic Delivery Platforms Of Antidepressantsmentioning
confidence: 99%
“…As discussed above, nanotechnology offers a remarkable potential to improve the therapeutic effect of antidepressants. Nevertheless, nano-drug delivery systems have been reported in several studies to cause neurotoxicity [ 73 ]. For example, in vitro studies and clinical trials indicated that nanoparticles exhibit minor or major toxicity effects depending on the degree of toxicity of the biopolymers [ 73 ].…”
Section: Toxicity Of Nano-based Antidepressantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, a search for “nanotechnology in pain” produced about 7975 publications from 1996. According to a review article from 2018 by Beiranvand and Sorori [137], the proper treatment of pain is still a major medical challenge; therefore, different approaches using various nano-formulated materials have been employed in the last decade. According to Moradkhani et al [138], analgesic drug delivery nanosystems have been applied in pain therapy due to their remarkable properties: enhanced drug delivery profile, increased drug action and bioavailability, targeted/sustained or prolonged drug release profile, stability in biological fluids, nontoxicity, carried drug protection up to the target cell population, and reduced side effects of the incorporated analgesic drugs [139].…”
Section: Pain and Cf Managementmentioning
confidence: 99%
“…Acute postoperative pain is one of the common complaints [ 1 , 2 ]. Its treatment is one of the important health-related issues and a number of guidelines have been recommended to treat the pain [ 3 , 4 ]. After surgery, pain assessment is considered as a fifth vital sign [ 5 ].…”
Section: Introductionmentioning
confidence: 99%